Characterization of antimicrobial and antioxidant performance of dihydroeugenol and its glycoside incorporated into whey protein isolate films - Resende, Déborah Braga; Simões, Luara Aparecida; Teixeira Fernandes, Natalia de Andrade; Luvizaro, Lucas Baldo; Dias, Marali Vilela; Carvalho, Diogo Teixeira; Piccoli, Roberta Hilsdorf; Schwan, Rosane Freitas; Dias, Disney Ribeiro (Frontiers in Food Science and Technology, 2023)
Bio-based plastics are gaining attention as environmentally friendly alternatives to traditional petroleum-based plastics in food packaging. Biodegradable films made from biocompatible macromolecules like polysaccharides and proteins offer promising solutions. This study investigated the effects of incorporating dihydroeugenol and glycoside into whey protein isolate (WPI) films to enhance their antimicrobial and antioxidant properties for food packaging. The findings showed that the glycoside film surpassed the dihydroeugenol film in inhibiting bacterial growth, forming larger inhibition halos against Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, and Salmonella Enteritidis (inhibition halos ≥ 15 mm). The glycoside film exhibited superior effectiveness against Gram-positive bacteria, indicating enhanced penetration through their cell membranes. Additionally, the synthesized compounds significantly boosted the antioxidant activity of the films compared to the control film without dihydroeugenol and glycoside. With a relatively low solubility (23±2.87% and 24±3.92% for dihydroeugenol and glycoside, respectively), these films are suitable for packaging and safeguarding food products with medium to high humidity. This study concluded that incorporating dihydroeugenol and its glycoside into WPI films holds great promise for developing active packaging solutions in the food industry. These films offer both antibacterial and antioxidant properties, particularly advantageous for food products with medium to high humidity.